Efficacy of Simplified Habit-Reversal on Stuttering Treatment in Home , School and Clinic - Behshid Garrousi; Ahmad Amir-Kafi; Azad Sa'aadat; Ashraf Sadat-Hosseini (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: Stuttering is a disorder that can cause serious personal, emotional and social problems. Based on its pathophysiology, different treatment approaches to stuttering are controversial. Behavioral treatment has been shown to be effective for stuttering.   In this study were mentioned to effectiveness of Simplified Habit-reversal as a behavioral approach for treatment of stuttering in Iranian children. Materials & Methods: Twelve students participated in this study was selected from 350 stuttered children in schools. After baseline assessment in three setting, simplified Habit -reversal was done for the children. Assessment (baseline) , treatment and booster sessions were done in the subject's home, school and clinic Assessment sessions were done at first -2nd-3th-4th-6th-12th-13th months after treatment. Post hoc tests were done by using paired t-test. Level of significance were considered equal on lest their 0.03 Results: Stuttering frequency was decreased in multiple assessment at home (P<0.03).these changes was observed in two other setting (P<0.02 in school, P0.05). Conclusion: Future researches about effectiveness of this method, especially in older cases and cases with co-morbidity in both sexes, are recommended.